A governança territorial no Circuito das Malhas do Sul de Minas Gerais - Fuini, Lucas Labigalini [UNESP] (Universidade Católica Dom Bosco, 2008)
This work has as central objective to characterize the importance of local coordination and regulation structures in the territorial dynamics of Circuit of the Meshes of Minas Gerais South, adding a new element to the study of the territorial competitiveness: the consideration of the governance and distribution of power forms in chains and productive systems with local and regional component fort.

Este trabajo tiene como objetivo central caracterizar la importancia de estructuras de coordinación y el Reglamento local en la dinámica territorial en el Circuito de las Mallas del Sur de Minas Gerais, en s' añadiendo un nuevo elemento a l' estudio de la competitividad territorial: la consideración de las formas de Gobierno y la distribución de poder en cadenas y sistemas productivos con muy componente local y regional.

Ce travail a comme objectif central caractériser l'importance de structures de coordination et le règlement locale dans la dynamique territoriale dans le « Circuit des Mailles du Sud de Minas Gerais », en s'ajoutant un nouvel élément à l'étude de la compétitivité territoriale: la considération des formes de « gouvernement » et la distribution de pouvoir dans des chaînes et des systèmes productifs avec fort composant local et régional.

Este trabalho tem como objetivo central caracterizar a importância de estruturas de coordenação e regulação locais na dinâmica territorial do Circuito das Malhas do Sul de Minas Gerais, agregando-se um novo elemento ao estudo da competitividade territorial: a consideração das formas de governança e distribuição de poder em cadeias e sistemas produtivos com forte componente local e regional.
The territorial governance in the Circuit of the Meshes of Minas Gerais South
El gobierno territorial en el Circuito de las Mallas del Sur de Minas Gerais
Keywords: Governance; Territory; Circuit of the meshes; Governança; Território; Circuito das malhas